Reorientating the economics programme at the IIUM - Mohd. Amin, Ruzita (IIUM Press, 2009)
Introduction : The Economics programme at the International Islamic University Malaysia (IIUM) has evolved over the years since it was first introduced, with the offering of the Bachelor of Economics programme by the Department of Economics, Kulliyyah (Faculty) of Economics & Management Sciences (then, called the Kulliyyah of Economics) as one of the two inaugural programmes of the IIUM when it was established in 1983. The Bachelor of Business Administration was later introduced in 1984, followed by the Bachelor of Accounting programme in 1987, both branching from the mother discipline of Economics. Two departments were also simultaneously established within the kulliyyah with the launching of these programmes, namely the department of Business Administration and the Department of Accounting. In addition......